Deoxyribonuclease 1-Mediated Clearance of Circulating Chromatin Prevents From Immune Cell Activation and Pro-inflammatory Cytokine Production, a Phenomenon Amplified by Low Trap1 Activity: Consequences for Systemic Lupus Erythematosus - Felux, Jasmin; Erbacher, Annika; Breckler, Magali; Hervé, Roxane; Lemeiter, Delphine; Mannherz, Hans Georg; Napirei, Markus; Rammensee, Hans-Georg; Decker, Patrice (Frontiers in Immunology, 2021)
Increased concentrations of circulating chromatin, especially oligo-nucleosomes, are observed in sepsis, cancer and some inflammatory autoimmune diseases like systemic lupus erythematosus (SLE). In SLE, circulating nucleosomes mainly result from increased apoptosis and decreased clearance of apoptotic cells. Once released, nucleosomes behave both as an autoantigen and as a damage-associated molecular pattern (DAMP) by activating several immune cells, especially pro-inflammatory cells. Deoxyribonuclease 1 (DNase1) is a major serum nuclease whose activity is decreased in mouse and human lupus. Likewise, the mitochondrial chaperone tumor necrosis factor receptor (TNFR)-associated protein-1 (Trap1) protects against oxidative stress, which is increased in SLE. Here, using wild type, DNase1-deficient and DNase1/Trap1-deficient mice, we demonstrate that DNase1 is a major serum nuclease involved in chromatin degradation, especially when the plasminogen system is activated. In vitro degradation assays show that chromatin digestion is strongly impaired in serum from DNase1/Trap1-deficient mice as compared to wild type mice. In vivo, after injection of purified chromatin, clearance of circulating chromatin is delayed in DNase1/Trap1-deficient mice in comparison to wild type mice. Since defective chromatin clearance may lead to chromatin deposition in tissues and subsequent immune cell activation, spleen cells were stimulated in vitro with chromatin. Splenocytes were activated by chromatin, as shown by interleukin (IL)-12 secretion and CD69 up-regulation. Moreover, cell activation was exacerbated when Trap1 is deficient. Importantly, we also show that cytokines involved in lupus pathogenesis down-regulate Trap1 expression in splenocytes. Therefore, combined low activities of both DNase1 and Trap1 lead to an impaired degradation of chromatin in vitro, delayed chromatin clearance in vivo and enhanced activation of immune cells. This situation may be encountered especially, but not exclusively, in SLE by the negative action of cytokines on Trap1 expression.